1990
DOI: 10.1128/jb.172.11.6372-6379.1990
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and analysis of the Bacillus subtilis rpsD gene, encoding ribosomal protein S4

Abstract: The rpsD gene, encoding ribosomal protein S4, was isolated from Bacillus subtilis by hybridization with oligonucleotide probes derived from the S4 amino-terminal protein sequence. Sequence analysis of the cloned DNA indicated that rpsD is likely to be monocistronic, in contrast to Escherichia coli rpsD, which is located in the a operon and is the translational regulator for a operon ribosomal protein gene expression in E. coli. The cloned gene was shown to map at position 2630 on the B. subtilis chromosome, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
30
0

Year Published

1991
1991
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…subtilis S4 compared with 82% for B. stearothennophilus versus B. subtilis [12] and 52% for E. coli versus B. subtilis [10]). It therefore appears that the pattern of phylogenetic relatedness derived from 16S rRNA sequence data can also be observed in an analysis of highly conserved ribosomal protein genes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…subtilis S4 compared with 82% for B. stearothennophilus versus B. subtilis [12] and 52% for E. coli versus B. subtilis [10]). It therefore appears that the pattern of phylogenetic relatedness derived from 16S rRNA sequence data can also be observed in an analysis of highly conserved ribosomal protein genes.…”
Section: Resultsmentioning
confidence: 99%
“…Transcription of the B. subtilis rpsD gene initiates at a near-consensus oA-type promoter sequence approximately 180 bp upstream of the start of the S4 coding sequence (10). Previous studies demonstrated that expression of an rpsDlacZ translational fusion is repressed in the presence of excess S4 (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The spx mutation appeared to have no effect on the level of primer extension product. The primer extension product of rpsD (ribosomal protein S4 [16]), transcript levels of which are not expected to change under the growth conditions tested, was included as a control.…”
Section: Resultsmentioning
confidence: 99%
“…As a first step in determining the flexibility of the structural requirements for tRNA Tyr for tyrS antitermination, E. coli tRNA Tyr was introduced into B. subtilis+ E. coli tRNA Tyr contains multiple differences at the primary sequence level from its B. subtilis homolog (Fig+ 2)+ These differences include some of the key tertiary interaction positions (Giege et al+, 1993); although the 15{48 trans interaction is maintained, the 26{44 cis interaction (G{U) Tyr is known to interact with the leader by pairing of the anticodon (CUA, outlined letters) with the specifier sequence (boxed UAG amber codon) and by pairing of the 39 acceptor end of the tRNA (UCCA, outlined letters) with the side bulge of the antiterminator (UGGA)+ The remainder of the tyrS leader is omitted for clarity (dashed lines)+ Numbering of the tyrS leader is relative to the start point of transcription (Henkin et al+, 1992)+ is replaced by A{C, the (47{45)(10{25) interaction [(U{C)(G-C)] is replaced by (U{G)(C-G), and the (13{22){47 interaction [(A{A){U] is replaced by (G{A){U in E. coli tRNA Tyr + The supF amber suppressor allele of tRNA Tyr , containing a CUA anticodon to match UAG amber codons (Kirsebom & Svard, 1992), was modified by introduction of an A73U mutation at the discriminator position of the tRNA to reduce possible interference by charged tRNA+ This substitution blocks tRNA Tyr charging by TyrRS (Bedouelle et al+, 1993), and it was previously demonstrated that this mutation in B. subtilis tRNA Tyr AMB, a supF analog, reduced amber suppression in vivo and permitted induction of a tyrS-lacZ fusion with a corresponding U222A substitution at the antiterminator and UAG specifier sequence during growth in rich medium (Grundy et al+, 1994)+ The mutant tRNA was inserted into plasmid pDG148 (Stragier et al+, 1988) so that expression would be directed by the IPTG-inducible Pspac promoter+ This construct was introduced into B. subtilis tester strains containing single-copy tyrS-lacZ fusions integrated into an SPb prophage+ Expression of the tyrS-lacZ AMB-U222A fusion in the absence of plasmid-directed tRNA synthesis was low, and IPTG-induced synthesis of tRNAs lacking a match at the specifier (pWT) or at the U222A position (pAMB) failed to significantly increase expression of the fusion (Table 1 Am -lacZ translational fusion, which contains an amber mutation in the ribosomal protein S4 coding sequence fused to a lacZ reporter (Table 1); this fusion was previously used to assay translational suppression (Grundy & Henkin, 1994b) An expression system that eliminated the requirement for the tRNA to provide the normal processing determinants was developed to facilitate generation of large numbers of variants of tRNA Tyr , some of which could be expected to alter these determinants+ The expression cassette (Fig+ 3) placed the first position of the tRNA (using an XmaI restriction site) at the transcription start point of the very strong B. subtilis rpsD promoter (Grundy & Henkin, 1990), so that the primary transcript would contain the mature 59 end of the tRNA (with a 59 triphosphate, rather than the monophosphate normally generated by RNaseP cleavage of a longer precursor tRNA)+ The 39 terminal A of the tRNA was placed immediately upstream of the 59 position of a variant of tRNA Gln , so that RNaseP cleavage at the 59 end of tRNA Gln , directed by tRNA Gln , would simultaneously lib...…”
Section: Resultsmentioning
confidence: 99%